LIVER CIRROCHIS MALIGNANT DEGENERATION : CASE REPORT - Bimantara, Nyoman Gede (E-Jurnal Medika Udayana; vol 3 no 3 (2014):e-jurnal medika udayana)
Liver cirrhosis is a chronic liver disease characterized by irreversible fibrosis , lobular structure and vascular disorganization , as well as regenerative nodules of hepat ocytes , which is the end result of hepatocellular damage . More than 40 % of asymptomatic patients with cirrhosis . In this state of cirrhosis found time routine health examination or at the time of autopsy . Liver cirrhosis can be caused by many things . The causes include infectious diseases , hereditary and metabolic diseases , drugs and toxins . In western countries the most common cause of liver cirrhosis is alcohol consumption , whereas in Indonesia is mainly caused by hepatitis B or C. The etiology of liver cirrhosis affects the handling of this disease . Therapy was conducted aiming to reduce the progression of the disease , avoid ingredients that can add to liver damage , prevention and treatment of complications . Treatment of liver cirrhosis requiring medical teamwork , patients , and families and the environment in the management of this disease .
Keywords: Systemic Lupus Erythematosus